2021
DOI: 10.1186/s12887-021-02761-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of pre-operative fistula diagnostics in anorectal malformations

Abstract: Background Surgical safety during posterior sagittal anorectal plasty (PSARP) for anorectal malformations (ARM) depends on accurate pre-operative fistula localization. This study aimed to evaluate accuracy of pre-operative fistula diagnostics. Methods Ethical approval was obtained. Diagnostic accuracy of pre-PSARP symptoms (stool in urine, urine in passive ostomy, urinary tract infection) and examination modalities (voiding cystourethrogram (VCUG),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…[ 29 ] The accurate delineation of pathological anatomy increases safety by minimizing avoidable surgical trauma or injuries to the urinary and genital tract. [ 31 ] Urinary tract injury may be predisposed to either by improperly performed distal colostogram providing incomplete information or to variation in the technique that the surgeons employ for pull-through. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 29 ] The accurate delineation of pathological anatomy increases safety by minimizing avoidable surgical trauma or injuries to the urinary and genital tract. [ 31 ] Urinary tract injury may be predisposed to either by improperly performed distal colostogram providing incomplete information or to variation in the technique that the surgeons employ for pull-through. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Cross table prone lateral X-ray, cystoscopy, voiding cystourethrography, and magnetic resonance imaging can also provide reliable knowledge about the level of the distal rectal pouch. [ 14 17 29 31 32 33 34 35 ] The stoma allows the pediatric surgeon to perform pressure augmented distal colostogram for better delineation of the anomaly. [ 17 ] albeit an operator-dependent investigation and carries a risk of radiation exposure and a bowel perforation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 (Figure 2A) Prior studies have reported an accuracy of 66% for colostogram and 58% for VCUG for identifying the level of the fistula. 20…”
Section: Voiding Cystourethrogram (Vcug)/genitogram and Colostogrammentioning
confidence: 99%
“…High-pressure colostogram (HPC) is considered the most effective method for diagnosing fistulas, but there is a lack of large-scale comparative study and the previous studies have some methodological issues [ 10 ]. Voiding cystourethrogram (VCUG) is helpful in the diagnosis of fistula [ 7 ], but there is controversy concerning when it should be performed [ 8 ]. Performing HPC and VCUG on all patients increases the dose of radiation and is unnecessary.…”
Section: Introductionmentioning
confidence: 99%